Linked Caracas: Hospital city (Revista de Ensino em Artes, Moda e Design, 2020)
The Linked Caracas project, winner of the 1st prize of the Competition for ParticipatoryProjects in Public Space organized by CCS City 450, is a critical exercise based on the conceptof inoperativity about “other” ways to “activate” the public space from of temporary interventionsthat promote the formation of relationships and ties between citizens, the city and thenature of the popular neighborhood Santa Rosa in Caracas, Venezuela. The so-called “HospitalCity” includes the encounter of Andrés Bello Avenue with San Julián Street, where the Children’sOrthopedic Hospital is located. Although traditionally many people gather in this sector,it does not have adequate spaces for pedestrian traffic or for universal accessibility, nor places of recreation for the inhabitants of the community. In this sense, the proposal brought togethera multidisciplinary group of people: architects, plastic artists, social activists and even institutions,groups and community organizations, which with the support of the inhabitants of thesector themselves managed to “activate” it through participatory work. in different instances.These types of ephemeral interventions, rather than concretely solving the problems of infrastructure,equipment or services of the most vulnerable urban sectors, open instances fordialogue, reflection and criticism about “other” ways and ways of making use of spaces likethis in our cities.
Keywords: inoperativity; public space; architecture; desing